(untitled) (Al-Aasar, 2025)
The Holy Qur’an presents a comprehensive framework for the moral, social, and ethical reformation of human society. It does not merely address individual spirituality but also lays down foundational principles for collective life, social justice, human dignity, and moral responsibility. This study explores the significance of the Qur’an in addressing social problems through a sociological lens, emphasizing its relevance to both individual conduct and societal organization. At the time of the Prophet Muhammad’s (PBUH) advent, Arabian society was plagued by tribal conflicts, economic exploitation, moral decay, and the absence of a structured legal and ethical system. Human rights were largely ignored, and violence, injustice, and social inequality were widespread. The Qur’an intervened as a transformative force by redefining social relations, establishing justice, promoting equality, and emphasizing mutual responsibility among individuals and communities. It provided clear guidance on social ethics, economic fairness, family structure, and conflict resolution, thereby reconstructing society on principles of compassion, accountability, and harmony. From a sociological perspective, the Qur’an addresses social issues by correcting value systems, reforming institutions, and cultivating moral consciousness. This paper highlights how Qur’anic teachings serve as enduring solutions to social problems by fostering balance between individual rights and collective welfare. The study concludes that the Qur’an remains a timeless source of social reform, offering principles that are applicable to contemporary societies facing moral, social, and ethical challenges.